Cover Image, Volume 10, Issue 4. (14th June 2019) - Peck, Sarah A.; Hughes, Katlyn D.; Victorino, Jose F.; Mosley, Amber L.
Abstract : The cover image is based on the Advanced Review Writing a Wrong: Coupled RNA Polymerase II Transcription and RNA Quality Control by Amber Mosley, Jose Victorino, Sarah Peck, and Katlyn Burriss. https://doi.org/10.1002/wrna.1529 Abstract : The cover image is based on the Advanced Review Writing a Wrong: Coupled RNA Polymerase II Transcription and RNA Quality Control by Amber Mosley, Jose Victorino, Sarah Peck, and Katlyn Burriss. https://doi.org/10.1002/wrna.1529